Lung Abscess: Literature Review of Risk Factors, Classification, Clinical Manifestations, Diagnosis, and Prevention - Nitzana, Lale Nubya; Hasanah, Mielosita; Mikailla, Romy Healthy; Anugrah, Yunan Prabu Jaya; Ilmiah, Janiya Abdila; Ajmala, Indana Eva (Jurnal Biologi Tropis, 2025)
A lung abscess is the formation of a thick-walled cavity filled with purulent material due to suppuration and necrosis of the lung parenchyma. Cases of lung abscess are relatively rare today and were most common in the pre-prebiotic era due to the lack of treatment for bacterial infections. This literature review aims to obtain information related to lung abscess its etiology, diagnostics, and treatment options. The article was compiled using a literature search through databases such as PubMed, ScienceDirect, and Google Scholar using the keyword "lung abscess." The findings indicate that lung abscess is a condition characterized by the formation of a pus-filled cavity resulting from suppuration and necrosis of lung tissue. This disease is commonly caused by anaerobic bacterial infection, although aerobic bacteria may also play a role. Despite its relatively low incidence today, lung abscess remains an important clinical problem as it can arise as a complication of pneumonia or tuberculosis. Diagnosis is established through medical history, physical examination, and supporting investigations such as radiology and sputum culture. Management includes long-term antibiotic therapy, drainage, and surgical intervention for refractory cases. Preventive efforts involve maintaining oral hygiene, reducing alcohol consumption, and avoiding aspiration risk factors. Therefore, comprehensive understanding of the definition, pathogenesis, clinical features, diagnosis, and management of lung abscess is essential to support clinical practice in pulmonary medicine.